2021
DOI: 10.3390/en14020437
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of Biodiesel Production from High-Acid-Value Waste Cooking Oil via a Microwave Reactor Using a Homogeneous Alkaline Catalyst

Abstract: In this study, low quality oils (waste cooking oils) with high acid value (4.81 mg KOH/g) were utilized as the feedstocks for a transesterification reaction enhanced by additional microwave power and the use of an NaOH catalyst. The kinetics of the transesterification reaction under different reaction times and temperatures was studied. It was found that in the microwave-assisted transesterification reaction, the optimum conditions under a microwave power of 600 W were as follows: an NaOH catalyst of 0.8 wt %,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 53 publications
(25 citation statements)
references
References 33 publications
6
19
0
Order By: Relevance
“…Moreover, very low catalyst concentrations may not accelerate the reaction towards the products to completion due to emulsification, which negatively affects the phase separation. To confirm this point, Hsiao et al [11] . revealed that when 0.4 wt % was applied instead of 0.2 wt % NaOH as a homogeneous catalyst, the biodiesel conversion rate jumped significantly from 16.3 % to reached 91.4 %.…”
Section: Biodiesel Production Techniquesmentioning
confidence: 91%
“…Moreover, very low catalyst concentrations may not accelerate the reaction towards the products to completion due to emulsification, which negatively affects the phase separation. To confirm this point, Hsiao et al [11] . revealed that when 0.4 wt % was applied instead of 0.2 wt % NaOH as a homogeneous catalyst, the biodiesel conversion rate jumped significantly from 16.3 % to reached 91.4 %.…”
Section: Biodiesel Production Techniquesmentioning
confidence: 91%
“…with those of other researchers. 46,59 Biodiesel contains more oxygen, which improves oxidation reactions and reduces CO while raising CO 2 emissions. The production of CO 2 is increased by increasing the applied load in the SCDE, which causes chemical reactions inside the combustion chamber due to higher fuel accumulation at maximum load.…”
Section: Emission Characteristics Analysismentioning
confidence: 99%
“…The saponification value (SV) and acid value (AV) were found out by below equations 45,46 SV=VbVs×56.1×0.5m, where, V b is the volume of blank titration (ml), V s is the volume of the oil titration (ml) and m is the mass of the oil (g).…”
Section: Materials and Proceduresmentioning
confidence: 99%
“…As these catalysts are dissolved in alcohol and glycerol, so they cannot be recycled again. In addition, the removal of these catalysts is very difficult which increases the cost of biodiesel 98.…”
Section: Technologies For Biodiesel Productionmentioning
confidence: 99%